The Legislative Matching Game: Committee Matching and Effective Legislating in the States. (June 2020) - Swift, Clint S.
Abstract: I argue that the value of a particular set of committee assignments for a legislator is dependent on that legislator's policy interests. By this, I mean that "good" assignments will match committee policy jurisdictions with member policy priorities. I develop this concept of committee-agenda matching and present a measure of this match for legislators in 12 state lower chambers. After some brief measure validation, I present a substantive application, demonstrating that this match poses serious consequences for individual legislator's ability to shepherd their bills through the legislative process.